Identification and Characterization of Fluoroquinolone Non-susceptible Streptococcus pyogenes Clones Harboring Tetracycline and Macrolide Resistance in Shanghai, China - Shen, Yinfang; Cai, Jiehao; Davies, Mark R.; Zhang, Chi; Gao, Kun; Qiao, Dan; Jiang, Haoqin; Yao, Weilei; Li, Yuefang; Zeng, Mei; Chen, Mingliang (Frontiers in Microbiology, 2018)
Streptococcus pyogenes, also known as group A Streptococcus (GAS), is one of the top 10 infectious causes of death worldwide. Macrolide and tetracycline resistant GAS has emerged as a major health concern in China coinciding with an ongoing scarlet fever epidemic. Furthermore, increasing rates of fluoroquinolone (FQ) non-susceptibility within GAS from geographical regions outside of China has also been reported. Fluoroquinolones are the third most commonly prescribed antibiotic in China and is an therapeutic alternative for multi-drug resistant GAS. The purpose of this study was to investigate the epidemiological and molecular features of GAS fluoroquinolone (FQ) non-susceptibility in Shanghai, China. GAS (n=2,258) recovered between 2011-2016 from children and adults were tested for FQ-non-susceptibility. Efflux phenotype and mutations in parC, parE, gyrA, and gyrB were investigated and genetic relationships were determined by emm typing, pulsed-field gel electrophoresis and phylogenetic analysis. The frequency of GAS FQ-non-susceptibility was 1.3% (30/2,258), with the phenotype more prevalent in GAS isolated from adults (14.3%) than from children (1.2%). Eighty percent (24/30) of FQ-non-susceptible isolates were also resistant to both macrolides (ermB) and tetracycline (tetM) including the GAS sequence types emm12, emm6, emm11 and emm1. Genomic fingerprinting analysis of the 30 isolates revealed that non-susceptibility may arise in various genetic backgrounds even within a single emm type. No efflux phenotype was observed in FQ non-susceptible isolates, and molecular analysis of the quinolone resistance-determining regions (QRDRs) identified several sequence polymorphisms in ParC and ParE, and none in GyrA and GyrB. Expansion of this analysis to 152 publically available GAS whole genome sequences from Hong Kong predicted 7.9% (12/152) of Hong Kong isolates harbored a S79F ParC mutation, of which 66.7% (8/12) were macrolide and tetracycline resistant. Phylogenetic analysis of the parC QRDR sequences suggested the possibility that FQ resistance may be acquired through inter-species lateral gene transfer. This study reports the emergence of macrolide, tetracycline, and fluoroquinolone multidrug-resistant clones across several GAS emm types including emm1 and emm12, warranting continual surveillance given the extensive use of fluoroquinolones in clinical use.